NASAL POLYPOSIS - Шиян, С.П.; Mitin, V. (World of Medicine and Biology, 2014)
In paper some modern views on the etiology, pathogenesis and treatment polypous rinosinuita. Analyzed links etiology and pathogenesis that we believe are most important in the development of nasal polyposis. There are several theories of nasal polyposis, but they are all fairly debatable and require further study and additions. It is safe to say that in the pathogenesis of nasal polyposis play an important role in chronic inflammation of the tissues, eosinophilic infiltration of tissues and tissue oxidative stress. Active eosinophils that infiltrate polyp tissue, produce large amounts of toxic proteins with various toxic effects. The aim of the study was based on histopathological methods is most convenient to classify polypoid tissue. Treatment of any disease should be based on the elimination of causal factors, but in most cases we do not have clarity in the etiology of nasal polyposis, therefore examined several groups of drugs for pathogenetic treatment of this disease. It was concluded that further search in this area should include both improved techniques of surgical treatment and the introduction of highly effective pharmacotherapy.
Keywords: polyposis; nasal cavity polyp